Relationship between the Inflammatory Molecular Profile of Breast Carcinomas and Distant Metastasis Development - Eiró, Noemí; González, Lucía; González, Luis O.; Fernandez-Garcia, Belen; Lamelas, Maria Luz; Marín, Laura; González-Reyes, Salomé; Casar, José Manuel del; Vizoso, Francisco J. (PLOS ONE, 2012)
Inflammatory conditions may promote tumor progression and aggressiveness. In previous reports, we found a group of breast cancer tumors characterized by metalloprotease-11 (MMP-11) expression by intratumoral mononuclear inflammatory cells (MICs), which was associated with distant metastasis development. Thus, in the present study we evaluated the relationship between MMP-11 expression by MICs, distant metastasis development, and a wide panel of inflammatory factors in breast carcinoma. In an initial approach, we analyzed 65 factors associated with tumor progression and inflammation, in a tumor population classified in good or bad prognosis, based on MMP-11 expression by intratumoral MICs. The most differentially expressed factors were then analyzed in a wider tumor population classified according to MMP-11 expression by MICs and also according to metastasis development. These analyses were carried out by Real-time PCR. The results showed that of the 65 starting factors analyzed, those related with MMP-11 expression by MICs were: IL-1, −5, −6, −8, −17, −18, MMP-1, TIMP-1, ADAM-8, −10, −15, −23, ADAMTS-1, −2, −15, Annexin A2, IFNβ, Claudin-3, CCL-3, MyD88, IRAK-4 and NFκB. Of them, factors more differentially expressed between both groups of tumors were IL-1, IL-5, IL-6, IL-17, IFNβ and NFκB. Thereafter, we confirmed in the wider tumor population, that there is a higher expression of those factors in tumors infiltrated by MMP-11 positive MICs. Altogether these results indicate that tumors developing worse prognosis and identified by MMP-11 expression by intratumoral MICs, shows an up-regulation of inflammatory-related genes.